The effect of an educational unit on the knowledge and breakfast eating behavior of college students - Roe, Donna V. (My University, 1979)
This study used 45 University of Wisconsin - Stout students, ages 18 to 25, enrolled in two Health Survey 366-101 classes. The design used was the pretest, posttest control design. One class, the treatment group, received a 3-day educational unit in nutrition. Each class completed a pretest and a posttest knowledge questionnaire and at the same time recorded their food intake for the previous 24-hour periods. The results were used to assess breakfast eating behavior. Knowledge increase was significant (p< .05). Adequate breakfast eating behavior, defined as meeting one-fourth of the Recommended Daily Dietary Allowances of the National Academy of Sciences, did not show any improvement. There was no correlation between the level of knowledge and breakfast eating behavior following this educational unit.
Keywords: Nutrition.; Students -- Nutrition.